2022
DOI: 10.1007/s00415-022-11439-7
|View full text |Cite
|
Sign up to set email alerts
|

Thrombolysis in central retinal artery occlusion: a retrospective observational study

Abstract: Background There is no evidence-based therapy for non-arteritic central retinal artery occlusion (NA-CRAO). Intravenous thrombolysis (IVT) with alteplase in a time window < 4.5 h may lead to a favorable outcome. Purpose of this study was to investigate the feasibility, efficacy and safety of IVT in patients classified as functionally blind. Methods We conducted a retrospective observational study of NA-CRAO-patients. All patients underwent an ophthalmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…AD sensitivity meta-analyses included CRAO patients with a baseline VA of 20/200 or worse, excluding two studies with a high risk of bias and substantial influence on outcomes (N = 602). 52,53…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…AD sensitivity meta-analyses included CRAO patients with a baseline VA of 20/200 or worse, excluding two studies with a high risk of bias and substantial influence on outcomes (N = 602). 52,53…”
Section: Resultsmentioning
confidence: 99%
“…AD sensitivity meta-analyses included CRAO patients with a baseline VA of 20/200 or worse, excluding two studies with a high risk of bias and substantial influence on outcomes (N = 602). 52,53 International Journal of Stroke, 19 (1) In AD-Design 1, among patients who received IVT-tPA within 4.5 h (Figure 3), 80.9% (CI: 65.7-93.0%; unadjusted rate: 80.0%) had VA improvement by ⩾0.1 logMAR, 74.3% (CI: 60.9-86.0%; unadjusted rate: 73.2%) had ⩾0.3 logMAR VA improvement, and 39.0% (CI: 25.6-53.1%; unadjusted rate: 39.2%) had a final VA of ⩾20/100. SMCC of 77.1% logMAR (CI: 47.1-107.1%) was reported after receiving IVT-tPA within 4.5 h.…”
Section: Aggregated-level Data Analysesmentioning
confidence: 99%
“…The results of ESR did not change the likelihood of GCA or any decision made using the combination of platelet count and CRP. These results give rise to crucial considerations when pursuing a faster initial diagnosis for dubious cases to facilitate prompt glucocorticoid treatment for an atypical clinical presentation of GCA or treatment for relevant differential diagnoses e.g., non-arteritic CRAO and the ongoing studies of time-critical intravenous alteplase [ 10 , 11 ]. It should be noted that ultrasound examination of the extra-cranial arteries may enable a rapid and immediate diagnosis of GCA in a rheumatological setting [ 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Or do we have enough information to make decisions earlier? Second, current studies are exploring intravenous alteplase in non-arteritic CRAO within 4 to 5 h after symptom onset [ 10 , 11 ]. In that context, evaluation of whether a CRAO is arteritic or non-arteritic needs to be performed as fast as possible, and one can question how much more value we obtain by waiting for the ESR result?…”
Section: Introductionmentioning
confidence: 99%
“…A meta-analysis of intravenous fibrinolytic therapy in CRAO found that the treatment can significantly improve vision (defined as the improvement of VA from 20/200 or worse at presentation to 20/100 or better) in up to 50% in patients presenting within 4.5 hours after the onset. 4 To lessen systemic side effects, intra-arterial thrombolytic therapy (IAT) with direct infusion and lowered total thrombolytic dose has been used with several studies showed promising results of IAT in terms of visual improvement 6,8,9,[11][12][13] , despite The European Assessment Group for Lysis in the Eye (EAGLE) trial, the only randomized control trial of IAT, was terminated before the study was completed, due to a higher rate of adverse events, although minor, in the IAT group, with similar efficacy in the IAT and conservative management groups. 14 Various vasodilators such as sublingual isosorbide dinitrate and intravenous glyceryl trinitrate have been used to increase retinal blood flow, to dislodge the embolus and allow it to migrate more peripherally.…”
Section: Introductionmentioning
confidence: 99%